Qual o lugar da fotografia contemporânea? - Carvalho, José Marcos Cavalcanti de (2016)
The work aims to address the relationships around the picture as visualities precursor that caused changes in relation to other artistic languages. Seeking similarities between these and contemporary photography, we undertook a journey that sought answers around the photography place in relation to other contemporary arts. The course was conducted through the trends and artistic movements and photography lined up like picturalism, Dadaism and Surrealism during their various uses as an object and as an expressive art materials and plastic through to other languages and images several orders that compete with this technology and that constitute the art scene. In the present work we place it on copyright, artistic, expressive and procedural framework determined by technology and languages taking into account their defilements, their contributions and their deviations. In the first chapter, we treat the relationships that are structured within a cultural perspective around the differences given on the day and especially in the polarizations of the artistic work and daily life, establishing distinctions between practices that will reflect the distinctions between doings. Mainly the differences on photographic practice, to establish beforehand our subsequent arguments at work. In the second chapter, built from historical photographic procedures a thesis that had already constituent elements of artistry in these, and they determined all a path that photography would travel trying to demonstrate that it is a fair means of expressive possibilities, though, was still a new field to be explored with varying articulation possibilities in artistic circles. Since its inception it had already said artistic qualities, and how other modalities also had plastic and expressive features, though, was not understood these parameters by some segments of society. We seek the picturalism trend the basis for our arguments, understanding that this above others, then, is the questions that we propose to discuss, and which in turn promotes maturation and a more emphatic attitude, more focal than other attempts photography establish earlier in the field of art. Between the second and third chapters we scale a map that was developed from the events of cultural history, art and photography relating them graphically providing the ability to visually establish the relationships between important points for photography. They were related 126 (one hundred and twenty six) events that we believe to be important and relevant, including the demarcation of the period between the world wars. It covers a period that begins in the historic discovery of photography until 2007. In the third chapter, we treat of the photographic technique of a procedural way in relation to the practice of learned photography, addressing the technical capabilities of expressive means in relation to the procedures in the photographic field and their correlations in contemporary art. In the fourth chapter, they are aligned with respect to the intersections of the issues we discussed in previous chapters, covering the ways in which photography is established as the object of multiple approaches in art and around this in their relations as privileged material in contemporary art. We treat these matters primarily a visual path established from selected portfolios of the artists included in the work: Eustaquio Neves, Vik Muniz and Laurence Gartel and relationships of their works with other productions that we believe relevant artistically. The photography’s status as art has changed in the course of its development making it currently one of the materials used in contemporary art. We aim to scale in the production of these three artists within their artistic contributions, looking through the production of such a response on our questions about the contemporary place of photography.